Analysis of Organa Pipe Resonance Frequency Utilizing Phyphox Application and Auditory Perception in Kundt’s Tube - Ledya Safira; Thasyara Safna; Anisa Pangestuti; Maya Shinta Saqila; Shinta Dewi; Ahmad Suryadi; Fuji Hernawati Kusumah (PT. ALHAFI BERKAH INDONESIA, 2023)
The use of the Phyphox application proves to be highly beneficial in attaining precise experimental data by leveraging existing technology. This application is freely downloadable for both Android and iOS platforms. The research aims to compare resonance frequency values using human auditory perception and the Phyphox application. The study utilizes a transparent glass organ pipe with a length of 100 cm, conducting three repetitions for each obtained pitch. The selected menu on the Phyphox application is 'audio amplitude,' which displays the maximum sound intensity through numerical dB readings and a graphical representation. Phyphox serves as an auxiliary tool for determining the maximum noise value in open-closed organ pipes to identify the resonance frequency. It is crucial to use the Phyphox application in a noise-free environment, as even the slightest noise can influence the displayed maximum noise values on the application. The results indicate that the relative error value in the Phyphox application is smaller compared to human auditory perception, with 0.25% < 0.27%. Therefore, it can be concluded that the values obtained through the Phyphox application are more accurate with a minimal margin of error.